Molecular characteristics, clinical significance, and cancer immune interactions of cuproptosis and ferroptosis-associated genes in colorectal cancer - Li, Yang; Wang, Ru-yao; Deng, Yu-jiao; Wu, Shao-hua; Sun, Xinti; Mu, Hong (Frontiers in Oncology, 2022)
Objective: Immunotherapy has evolved as a critical option to treat diverse cancers. The active response to immunotherapy relies on the unique interaction between cancer and the tumor microenvironment (TME). Cuproptosis, a novel form of cell death, is highly linked to mitochondrial metabolism and mediated by protein lipoylation. Ferroptotic damage can trigger inflammation-associated immunosuppression in the tumour microenvironment, thus favouring tumour growth. However, the association between Cuproptosis/Ferroptotic and clinical outcome, immune cell infiltration, and immunotherapy remains unknown in Colorectal cancer (CRC). Methods:We systematically evaluated 33 cuproptosis and ferroptosis-related genes and comprehensively identified the correlations between cuproptosis and ferroptosis-related genes with transcriptional patterns, prognosis, and clinical features. PCA_score was used to quantify the prognostic genotype for each patient. We then assessed their value in CRC prognostic prediction and treatment response. Results: The survival time of patients in the low expression group of cuproptosis and ferroptosis-related genes was better than that in the high expression group. We identified two distinct prognosis-associated molecular subtypes and observed an association between clinical information and prognosis. The enrichment analysis of differential genes associated with prognosis showed that the main enrichment was related to biological processes such as metastasis and metabolism. Next, the PCA_score for predicting overall survival (OS) was established and its reliable predictive power in CRC patients was confirmed. Furthermore, we created a highly reliable nomogram to facilitate the clinical feasibility of the PCA_score. We also found that the immunomodulatory mAbs, PD-L1 and CTLA4, were highly expressed in the low PCA_score score group, and the difference was statistically significant. Conclusion: Overall, the PCA scores of prognostic differential genes in the cuproptosis and ferroptosis-related genes clusters were strongly associated with clinical characteristics, prognosis, and immunotherapy in CRC patients. This study is helpful to explore more effective immunotherapy strategies for CRC.